Mechanical behavior of natural fiber composites - Milanese, Andressa Cecilia [UNESP]; Hilario Cioffi, Maria Odila [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (Elsevier B.V., 2011)
The use of natural fibers as reinforcement in polymeric composites for technical applications has been a research subject of scientists during the last decade. There is a great interest in the application of sisal fiber as substitutes for glass fibers, motivated by potential advantages of weight saving, lower raw material price, and ecological advantages of using green resources which are renewable and biodegradable.Castor oil, a triglyceride vegetable that has hydroxyl groups, was reacted with 4,4' diphenylmethane diisocyanate (MDI) to produce the polyurethane matrix. Woven sisal fibers were used untreated and thermal treated at 60 C for 72h, and the composites were processed by compression molding.The present work study tensile behavior at four composites: dry sisal/polyurethane, humid sisal/polyurethane, dry sisal/phenolic and humid sisal/phenolic resin. The moisture content influences of sisal fibers on the mechanical behaviors were analyzed.Experimental results showed a higher tensile strength for the sisal/phenolic composites followed by sisal/polyurethane, respectively. In this research, sisal composites were also characterized by scanning electron microscopy. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of ICM11
Keywords: sisal fiber; castor oil based polyurethane resisn; phenolic resin; tensile strength; scanning electron microscopy